Benefits of group compassion-focused therapy for treatment-resistant depression: A pilot randomized controlled trial - Asano, Kenichi; Tsuchiya, Masao; Okamoto, Yoko; Ohtani, Toshiyuki; Sensui, Toshihiko; Masuyama, Akihiro; Isato, Ayako; Shoji, Masami; Shiraishi, Tetsuya; Shimizu, Eiji; Irons, Chris; Gilbert, Paul (Frontiers in Psychology, 2022)
Major depression is one of the most common mental health problems worldwide. More than one-third of patients suffer from treatment-resistant depression (TRD). In this study, we explored the feasibility of group compassion-focused therapy (CFT) for TRD using a randomized controlled trial with two parallel groups. Eighteen participants were randomly allocated to the intervention group (CFT and usual care) and control group (usual care alone) and a participant in each group withdrew. Participants in the intervention group received a 1.5-h session every week for 12 weeks. The effects of the intervention on the participants’ scores were calculated using a linear mixed model. There was a larger reduction in their depressive symptoms and fears of compassion for self and a greater increase in their compassion for self compared to the control group participants. The reliable clinical indices showed that in the CFT (intervention) group, three of nine participants recovered (33%), two improved (22%), two recovered but non-reliably (22%), and the condition of two remained unchanged (22%). These findings indicate adequate feasibility of group CFT for TRD in Japanese clinical settings. Clinical trial registration [https://clinicaltrials.gov/], identifier [UMIN 000028698].